Formy organizacji controllingu w małych i średnich przedsiębiorstwach - Nowosielski, Stanisław (Implementing Controlling in Small and Medium Enterprises., 2006)
The article presents different organizational solutions of controlling implementation in small and medium enterprises. Their characteristics are described, as well as the criteria of estimating the solutions. The author indicates the rules of choosing the model suitable for a specific company, with the application of multidimensional comparative analysis.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1101, s. 53-61